Autoimmunity in idiopathic epilepsies and encephalopathies of childhood - Wright, S (2014)
Immune mechanisms are thought to be involved in the pathological disease process in a number of childhood epileptic syndromes and encephalitis. Of particular interest is the occurrence of autoantibodies to essential neuronal proteins, for example the N-methyl-D-aspartate receptor (NMDAR), in the blood and spinal fluid in some of these patients. The aims of this study were: to examine the sera of newly diagnosed paediatric epilepsy patients for specific neuronal autoantibodies, correlate to epilepsy phenotype and disease outcomes; to investigate the pathogenicity and epileptogenicity of central nervous system autoantibodies (CNS) in vivo; and to test new therapies in vitro and in vivo based on the potential pathogenic mechanisms. In 290 paediatric patients with new-onset epilepsy and seizures tested for CNS autoantibodies, 11.4% were positive (33/290 versus 8/112 in controls; p=0.01, Fisher's exact test). Previously unreported contactin-2 antibody positive and contactin-associated-protein 2 (CASPR2) antibody positive epilepsy patients were described. Patients with 'focal epilepsy of unknown cause' were more likely to be antibody positive. To test the pathogenicity and epileptogenicity of these antibodies, a novel in vivo telemetry system was used to continuously record electroencephalogram (EEG) in mice injected into the cerebral lateral ventricle with NMDAR antibody (NMDAR-Ab) positive immunoglobulin (IgG). Although no spontaneous seizures were seen, mice challenged with the pro-convulsant pentylenetetrazole (PTZ) had increased seizure susceptibility, and more epileptiform "spikes" in the EEG after PTZ compared to healthy control (HC) IgG injected mice. Seizure susceptibility strongly correlated with binding intensity of NMDAR-Ab IgG analysed in post-mortem tissue. Given the hypothesis this epileptogenic effect was mediated by NMDAR-Abs internalising cell surface NMDARs, and to try and rescue this deficit, a neurosteroid, pregnenolone sulphate (PregS) known to increase NMDAR cell surface expression, was therapeutically used. This approach worked in vitro, and although in vivo effects were not yet established, treatment with neurosteroids may be beneficial for autoantibody mediated neurological disease.